Retrospective analysis of pedagogical techniques of forming students’ creative abilities - Cherednichenko, Galina; Kunytsia, Lyudmila; Shapran, Ludmila (My University, 2013)
Basic pedagogical technologies of forming of creative abilities of students are: developing training, theory of development of technical creation and theory of decision of inventor tasks (TRVZ), heuristic training, heuristic and module training are considered in this article.В статті розглянуті основні педагогічні технології формування творчих здібностей студентів, а саме: розвиваюче навчання, теорія розвитку технічної творчості і теорія вирішення винахідницьких задач (ТРВЗ), евристичне навчання, евристично-модульне навчання.
Keywords: педагогічні технології; творчі здібності; педагогические технологии; творческие способности; pedagogical technologies; creative abilities; кафедра ділової іноземної мови та міжнародної комунікації